TEACHING INDONESIAN CONCEPTS OF CULTURE THROUGH PAMALI - Budi Rahmat Setiawan (ELTIN Journal, 2024)
Pamali teaches the young generations of Indonesia to behave and act decently according to where they live. This is a strong term that brings fear to Indonesians because it contains prohibitions and most often causes that cannot be logically accepted. This research aims to show international readers how Indonesians teach the next generations through pamali (forbidden acts) found in an Indonesian comic. In this research, cultural conceptualization by Sharifian which is supported by Sibarani in his anthropolinguistic theory was used. The research is conducted using the descriptive–qualitative method. The data on pamali utterances are taken from an Indonesian comic book. It is because there is a very limited written source for pamali. The research uses the categorization of the cultural concepts seen in the dictions used. This study aims to find the  concept of Indonesian culture. The results revealed that the use of many kinds of word classes that can be interpreted to show the concept of life of Indonesians. The concept teaches us about the people of Indonesia, the food, the daily activities, the sacred symbols, as well as the environment of Indonesia.